Natural Regeneration of Parkia biglobosa (Néré): Status and variation along the South-North climatic gradient in Mali - Kelly, Bokary Allaye; Kouyaté, Amdou Malé; Dembélé, Sidiki Gabriel (Current Botany, 2022)
Parkia biglobosa offers food, medicine and income to rural populations. A study, was undertaken in three agro-climatic zones in southern Mali, to characterise P. biglobosa populations. Plots of 0.25 ha each were established in fields and fallows and adult trees in the plots were monitored. Natural regeneration was monitored in five subplots of 12.5 m x 12.5 m = 156.25 m2 each within each plot and data were collected from 2019 to 2021. Natural regeneration of P. biglobosa was found to be very weak in all sites. The mean density of seedlings varied from 11 to 24 seedlings ha-1 with a decreasing trend from 2019 to 2021. In Zanzoni, where the weakest regeneration was observed, the density varied from 0 to 8 seedlings ha-1. The highest density of seedlings was observed in Somasso in 2019 (42 seedlings ha-1) and 2020 (30 seedlings ha-1). In 2021, the highest density was observed in Diou (25 seedlings ha-1). The weakness of natural regeneration is very alarming for this tree species facing several other threats (ageing and decreasing adult tree populations, sanitary constraints, several pressures, etc.). It is therefore very important and imperative to investigate ways for regenerating the species for its sustainability and for maintaining the parklands biodiversity. Artificial regeneration (planting), could be the one and ultimate way to ensure the sustainability of P. biglobosa.